Ectopic ACTH syndrome in a dog with a mesenteric neuroendocrine tumour: a case report - Castillo, V. A. (2014)
Ectopic ACTH secretion is provoked by extra-pituitary tumours that secrete ACTH, constituting an infrequent type of Cushing Syndrome in the dog. Neuroendocrine tumours (NET) are characterised by the synthesis of peptides with hormone activity. A dog with clinical diagnosis of Cushing?s syndrome and presenting an abdominal tumour located in the area of the left adrenal gland was sent to the hospital. Cortisol was not inhibited at four and eight hours after the application of low-dose dexamethasone and the cortisol/creatinine ratio was elevated (93 × 10-6, reference values < 10 × 10?6). Plasma ACTH measurements were high (28.6 pmol/l, reference values 5.5?14.3 pmol/l). On computed tomography, the tumour was found in the meso-epigastrium, with both adrenal glands hyperplasic and no alteration of the pituitary image. The tumour was located between the two layers of the meso-colon and was removed using laparoscopy. After surgery, ACTH concentrations became normal and clinical signs remitted. The histopathological diagnosis was NET, with positive ACTH immunostaining.